Biohydrogen production using kitchen waste as the potential substrate: A sustainable approach. (May 2021) - Srivastava, Neha; Srivastava, Manish; Abd_Allah, Elsayed Fathi; Singh, Rajeev; Hashem, Abeer; Gupta, Vijai Kumar
Abstract: This review explores the sustainable feasibility of kitchen wastes to implement as an effective substrate for biohydrogen production through dark fermentation. Being organic in nature, kitchen wastes are enomerous source of nutrients and carbohydrate, which are produced in huge quantity in our daily life, and therefore can be potentially used for biohydrogen production through microbial technique. The review discussed in detail about the impact of kitchen waste, its availability and sustainability on the biohydrogen production process along with future scope at industrial scale for the production of sustainable and renewable energy. In addition, recent advances, and their possibility to enhance the fermentative biohydrogen production using kitchen waste have been covered. Emphasis is also made on the application of nanomaterials to increase the yield of biohydrogen production and to make the entire process more economical and sustainable while using kitchen wastes as substrate for the microbial fermentation. Finally, advantages, limitations and future prospects of the process of biohydrogen production using kitchen wastes as potential substrate have been discussed. Highlights: Kitchen waste as the potential substrate for biohydrogen production is reviewed. Impact of kitchen waste on biohydrogen production mode has been reviewed. Kitchen waste as substrate to improve the biohydrogen yield is explored. Emphasis has been made on food waste to value added product & waste management. Rollback in food wastes to biohydrogen process have been discussed with future scope.